Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian pada Game Genshin Impact Menggunakan Klasifikasi Naive Bayes - Wiranata, Hadi; Sucipto, Sucipto; Nugroho, Arie (Forum Kerjasama Pendidikan Tinggi, 2025)
The growth of the online gaming industry has led to the emergence of microtransaction-based business models, where players can purchase virtual items using real money. One of the games implementing this model is Genshin Impact, which has attracted a wide audience through its gacha system and diverse character content. This study aims to identify the factors that influence players' decisions to purchase virtual items in Genshin Impact using the Naive Bayes classification method. Data were collected through an online questionnaire involving 314 respondents. The analyzed variables include play duration, satisfaction with the gacha system, costumes, storyline, social influence, and previous purchase experience. The model was developed using the Gaussian Naive Bayes algorithm and validated through the Stratified K-Fold Cross-Validation method. The results show that the model achieved an accuracy of 80.57% in classifying purchase decisions. While the model performed well in identifying players who made purchases, its performance in classifying non-purchasing players requires improvement. This research is expected to serve as a reference for understanding player purchasing behavior and developing digital marketing strategies in the online gaming industry.